Optical Visualization of Stretchable Serpentine Interconnects using Chiral Liquid Crystal Elastomers - Sang Hyun Han; Jun Hyuk Shin; Hak Jun Yang; Seungmin Nam; Ji Yoon Park; Su Seok Choi (Advanced Science)
Abstract The shapes and structures of stretchable interconnects are pivotal in determining their functionality, allowing them to withstand bending, stretching, and twisting while maintaining their operational integrity. However, all stretchable interconnects are subjected to dynamically changing, non‐uniform strains during mechanical deformation. Therefore, achieving an accurate understanding of stretchable interconnect properties, including tracking and analyzing these dynamic, non‐uniform strains in real‐time, remains a challenging endeavor. Herein, a method for analyzing the strain behavior of stretchable interconnects using a chiral liquid crystal elastomer (CLCE), which exhibits immediate structural color changes of nano periodic molecular arrangement in response to dynamic stretching deformations, is presented. Beyond the uniform color change of simple CLCE, by further engineering the modulus and shape geometry of the serpentine CLCE, an intuitive strain capturing visualization of dynamically changing serpentine structures is performed. Moreover, by expanding the serpentine CLCE into a 2 × 2 array, the real‐time strain distribution of the stretchable interconnects under various multi‐stretching properties (uniaxial and biaxial) is investigated. This optical visualization provides an accurate and precise understanding of the structure of stretchable interconnects under dynamic stretching conditions and is a promising breakthrough to enable enhanced design and optimization of stretchable serpentine structures for broadband stretchable applications.